Proceedings of the 2016 24th ACM SIGSOFT International Symposium on Foundations of Software Engineering 2016
DOI: 10.1145/2950290.2950344
|View full text |Cite
|
Sign up to set email alerts
|

A large-scale empirical comparison of static and dynamic test case prioritization techniques

Abstract: The large body of existing research in Test Case Prioritization (TCP) techniques, can be broadly classified into two categories: dynamic techniques (that rely on run-time execution information) and static techniques (that operate directly on source and test code). Absent from this current body of work is a comprehensive study aimed at understanding and evaluating the static approaches and comparing them to dynamic approaches on a large set of projects.In this work, we perform the first extensive study aimed at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 58 publications
(135 reference statements)
1
58
2
Order By: Relevance
“…Third, the T CP add technique does not outperform the T CP tot strategy, contradicting findings from past studies where the T CP add has been shown to perform best overall [21], [46], [62]. Fourth, the results of the Tukey HSD test suggest that for APFD, the performance of the TCP programs does not vary in a statistically significant manner.…”
Section: A Rq 1 : Tcp Effectiveness On Real Faultscontrasting
confidence: 60%
See 3 more Smart Citations
“…Third, the T CP add technique does not outperform the T CP tot strategy, contradicting findings from past studies where the T CP add has been shown to perform best overall [21], [46], [62]. Fourth, the results of the Tukey HSD test suggest that for APFD, the performance of the TCP programs does not vary in a statistically significant manner.…”
Section: A Rq 1 : Tcp Effectiveness On Real Faultscontrasting
confidence: 60%
“…While there are many types of existing TCP techniques [16], [23], [29], [38], [66], [80], one common dichotomous classification, static [31], [42], [81] and dynamic techniques [18], [19], [22], [41], [53], [65], [72], [79], relates to the type of information used to perform the prioritization. Static approaches utilize information extracted from source and test code and dynamic techniques rely on information collected at runtime (e.g., coverage information per test case) to prioritize test cases [46]. Additional classifications exist, such as the distinction between white-box and black-box techniques [30].…”
Section: A Tcp Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach has been successfully used for bug localization in the BLUiR system before [18]. Static test prioritization operates without change data and tries to spread similar tests to cover many concepts (diversity) or most of the program (coverage) up-front [10]. Topic models have been used by Thomas, Hemmati, Hassan, and Blostein [21] to model these concepts as topics over lexical features and hence address the concept coverage problem from a lexical viewpoint.…”
Section: :21mentioning
confidence: 99%